New York City Cab Drivers' Labor Supply Revisited: Reference-Dependent Preferences with Rational-Expectations Targets for Hours and Income - Crawford, Vincent P; Meng, Juanjuan (American Economic Review, 2011)
This paper proposes a model of cab drivers' labor supply, building on Henry S. Farber's (2005, 2008) empirical analyses and Botond Kőszegi and Matthew Rabin's (2006; henceforth “KR”) theory of reference-dependent preferences. Following KR, our model has targets for hours as well as income, determined by proxied rational expectations. Our model, estimated with Farber's data, reconciles his finding that stopping probabilities are significantly related to hours but not income with Colin Camerer et al.'s (1997) negative “wage” elasticity of hours; and avoids Farber's criticism that estimates of drivers' income targets are too unstable to yield a useful model of labor supply. (JEL J22, J31, L92)